Evaluation of a constant rate intravenous infusion of dexmedetomidine on the duration of a femoral and sciatic nerve block using lidocaine in dogs - Stabile, Marzia; Lacitignola, Luca; Acquafredda, Claudia; Scardia, Annalaura; Crovace, Antonio; Staffieri, Francesco (Frontiers in Veterinary Science, 2023)
Objectives: The aim of the study was to investigate the effects of 1 μg /kg/h CRI of dexmedetomidine as adjuvant associated to lidocaine perineurally administered, on sensory and motor blockade for femoral and sciatic nerve blocks in dogs undergoing stifle surgery. Materials and methods: Client-owned dogs referred for TTA surgery were enrolled in this prospective, randomized, blinded study. Electrolocation-guided sciatic and femoral nerve blocks, with lidocaine 2% (0.15 mL/ kg), were performed using the parasacral and lateral pre-iliac approach respectively. After the local block execution, a systemic infusion of a saline solution (C group) or dexmedetomidine (D group) was started in CRI at 1 ml/kg/h and continued until the end of surgery. Dexmedetomidine was infused at the dose of 1 μg/kg/h. Respiratory and hemodynamic parameters were recordered during surgery. Sensory and motor blockade were evaluated at 30, 60, 120, 180, and 240 minutes after extubation, by response to forceps pinch on skin innervated by the sciatic/femoral nerves, and by observing the ability to walk and proprioception. Analgesia was monitored with SF-GCPS. Methadone IM was administered as rescue analgesia. Intraoperative data were analysed by ANOVA test, while postoperative data were analysed by independent two-tailed t-test and Kaplan-Meier test (p < 0.05). Results: Twenty dogs were included in the study (10/group). A significant difference in the recovery of the sensory nerve function was found among groups. The mean duration of the sensory blockade for femoral and sciatic nerves was longer (p < 0.001) for group D [168 (146 –191, 95% CI), 161 (143–179, 95% CI) minutes] than for group C [120 (96.1-144, 95% CI), 120 (96.1-144, 95% CI)]. No differences in the recovery of patella and tibial reflexes, proprioceptive function and ability to walk were found among groups. The overall postoperative rescue analgesia requirement was significatively different (P=0.019) between groups, with an incidence of 5/10(50%) patients in D group and 10/ 10(100%) in C group. Conclusion: Dexmedetomidine administered in CRI(1 μg /kg/h) combined with local lidocaine increases the duration of the sensory block of sciatic and femoral nerve blocks and reduces the requirement for additional analgesia during the immediate postoperative hours.